Kemampuan Komunikasi Matematis dalam Pembelajaran Problem Based Learning dengan Teacher Feedback Ditinjau dari Gaya Kognitif Siswa SMP - Evariyani Evariyani; Kartono Kartono; Tri Suminar (Journal on Education, 2023)
The purpose of this study was to test the effectiveness of the Problem Based Learning model with teacher feedback on junior high school students' mathematical communication skills. This research method is a combination or mixed research which is also known as the Mixed Method. The model used in this study is a Sequential Explanatory type. The subjects of this study were students of SMP N 3 Kandangan in semester II of the 2021/2022 academic year. The quantitative sampling technique used is cluster random sampling. The preparation and collection of data was carried out based on quantitative and qualitative data. Quantitative data were taken from the pretest stage which was carried out in the experimental class and control class up to the posttest which was carried out in the same class. Meanwhile qualitative data were obtained from observation sheets of teacher and student activities. The implementation of PLB learning with teacher feedback was effective on students' mathematical communication skills with teacher feedback better than students who were taught with the Discovery learning learning model. The results showed that strong FI students achieved written and oral mathematical communication skills capable of completing 4 indicators. Students with moderate FI cognitive style on mathematical communication skills meet 4 indicators for oral and written communication skills. Students with a low FI cognitive style fulfill 1 indicator and students with moderate FD cognitive style in mathematical communication skills fulfill 3 indicators for oral and written communication skills. Students with low FI cognitive style meet 1 indicator.